2018
DOI: 10.18632/oncotarget.24678
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide-mediated suppression of miR-182-5p is associated with potent anti-oxidant effects through up-regulation ofSESN2

Abstract: Arsenic trioxide (ATO) is a traditional Chinese medicine that can induce oxidative stress for treatment of cancer cells. However, ATO may generate anti-oxidative responses to compromise the cytotoxic effect, but the underlying mechanisms remain unclear. Here we found that ATO could inhibit miR-182-5p expression in patient-derived primary S1 glioblastoma (GBM) cells accompanied by up-regulation of Sestrin-2 (SESN2) mRNA, a known anti-oxidant molecule. This phenomenon was also detected in a U87MG glioma cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 80 publications
2
16
0
Order By: Relevance
“…Both UVB and UVA induce Sesn2 upregulation in melanocytes and melanoma cells suggesting the oncogenic role of Sesn2 in melanoma skin cancer (Zhao et al, 2017). The gene expression of Sesn2 upregulated by miR182-5p suppression in arsenic treatment functions as an antioxidant in Uppsala 87 malignant glioma (U87MG), human lung adenocarcinoma H1299, and A549 cell lines (Lin et al, 2018). Sesn2 would promote colorectal cancer cell growth in the iron-rich environment by suppressing ROS (Kim et al, 2019).…”
Section: Sestrins In Nutrient Stress-sensing and Metabolic Dysfunctionmentioning
confidence: 99%
“…Both UVB and UVA induce Sesn2 upregulation in melanocytes and melanoma cells suggesting the oncogenic role of Sesn2 in melanoma skin cancer (Zhao et al, 2017). The gene expression of Sesn2 upregulated by miR182-5p suppression in arsenic treatment functions as an antioxidant in Uppsala 87 malignant glioma (U87MG), human lung adenocarcinoma H1299, and A549 cell lines (Lin et al, 2018). Sesn2 would promote colorectal cancer cell growth in the iron-rich environment by suppressing ROS (Kim et al, 2019).…”
Section: Sestrins In Nutrient Stress-sensing and Metabolic Dysfunctionmentioning
confidence: 99%
“…Furthermore, these authors showed that overexpressed sestrin 2 was a marker for poor prognosis in lung cancer by analyzing the PrognoScan database and Kaplan–Meier Plotter [ 44 ]. Additionally, by analyzing data from the Gene Expression Omnibus and Cancer Genome Atlas analysis, Lin et al revealed that the survival time for lung cancer patients with lower sestrin 2 expression was significantly prolonged [ 45 ].…”
Section: The Alteration Of Sestrin 2 Gene Expression In Various Cancersmentioning
confidence: 99%
“…Many purified compounds from dietary sources have been investigated for their anticancer activities through a direct modulation of SESN expression [80,81,82,83,84,85,86,87,88].…”
Section: Sestrins and The Therapeutical Management Of Cancermentioning
confidence: 99%
“…Puzzlingly, ATO can also promote antioxidant activities that can compromise its desired effects in a context-dependent manner [120]. Liang-Ting et al reported that ATO suppresses miR-182-5p expression in several cancer cell lines, correlating with the upregulation of SESN2 mRNA [85]. The pre-treatment with the free radical scavenger N-acetyl-cysteine (NAC) reduced oxidative stress and ATO-mediated suppression of miR-182-5p as well as the associated enhancement of SESN2 expression.…”
Section: Sestrins and The Therapeutical Management Of Cancermentioning
confidence: 99%
See 1 more Smart Citation